ANALYSIS OF FREIGHT RATES FOR BULK SOYBEAN WITHIN THE UNI- AND MULTI-MODAL TRANSPORT SYSTEM - Souza, Rodrigo Oliveira; Cremasco, Camila Pires [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP] (Centro Universitario de Maringa, 2016)
Transport is the link between producing and processing units within agribusiness, featuring an important participation in the country´s economy. Although it is the displacement of enormous amount of cargo, most products have low aggregated value and high transport value. This is the case of soybean, a commodity in which freight rates are highly significant in the product´s final price. It is very important to identify transport means and ways that reduce freight rates. Current research analyzes transport of soybean from São Simão GO Brazil to Osvaldo Cruz SP Brazil, the former town is a great producer of the commodity and the latter town is a great processer of the same. Research also compares the uni- and multimodal road transport system used. Data were analyzed by statistics and simulation. Results show that the multimodal system, within the route investigated, provides a significant decrease in the final freight rate (33.3%) when compared to that in the exclusively road transport.
ANÁLISE DOS VALORES DE FRETE DA SOJA A GRANEL NOS SISTEMAS UNIMODAL E MULTIMODAL DE TRANSPORTE
Keywords: Freight; Logistics; Multimodal transport; Quantitative methods